Resumes for dummies - DeCarlo, Laura, author (Hoboken, NJ : John Wiley & Sons, Inc., 2019)
We've all been there: it's time to apply for a job or internship and you have to create or revise your resume. Many questions pop in your head. What do employers want? What skills should I highlight? How do I format this? How do I get noticed? But resume writing doesn't have to be a daunting task. The latest edition of Resumes For Dummies answers all of these questions and more--whether you're a resume rookie, looking for new tips, or want to create that eye-catching winning resume. In this trusted guide, Laura DeCarlo decodes the modern culture of resume writing and offers you insider tips on all the best practices that'll make your skills shine and your resume pop. Let's start writing!.